MicroRNA-Mediated In Vitro and In Vivo Direct Conversion of Astrocytes to Neuroblasts - Ghasemi-Kasman, Maryam (PLoS One, 2015)
BACKGROUND: The conversion of astrocytes to neuroblasts holds great promise for treatment of neurodegenerative and traumatic brain diseases. METHODOLOGY AND PRINCIPAL FINDINGS: Here we have shown that adult human astrocytes could be reprogrammed to neuroblasts by miR-302/367, both in vivo and in vitro. However, the reprogramming of adult mouse astrocytes to neuroblasts required valproic acid (VPA), a histone deacetylase inhibitor. Following induction of astrocytes toward neurons the expression of pluripotency markers were not detected, which suggested direct cell conversion. We did not observed tumor formation during two months follow up. CONCLUSIONS AND SIGNIFICANCE: These results show that neuroblasts can be generated directly from adult human and mouse astrocytes by miR-302/367-driven induction. This approach seems promising for converting glial scar cells into neuroblasts in a wide range of neurological diseases.